Sharing management: Three ethical scenarios - Dwiggins, Cyril (Journal of business ethics, 1986)
How might a transition from closely-held to shared management help or hinder the presence of the ethical in a corporation? I propose three fictional scenarios according to which such a transition might occur. In one, managerial power is shared, but without any examination of the firm's presuppositions. In another the presuppositions are shared as well, but only insofar as top management seeks to generate cultic enthusiasm for the ‘corporate family’. In the third scenario the firm's presuppositions are discussed openly by all employees. I argue that only this third scenario embodies the conditions which make it possible for a firm to be moral.